here we can use energy conservation
like initial kinetic + potential energy is always conserved and it will be same at all points
so we can say
[tex]KE_i + PE_i = KE_f + PE_f[/tex]
[tex]\frac{1}{2}mv_i^2 + mgh_1 = \frac{1}{2}mv_f^2 + mgh_2[/tex]
now we can plug in all the given values in it
[tex]v_i = 0[/tex]
[tex]h_1 = 443 m[/tex]
[tex]h_2 = 221 m[/tex]
[tex]\frac{1}{2}m*0 + m*9.8*443 = \frac{1}{2} m*v_f^2 + m*9.8*221[/tex]
now divide whole equation by mass "m"
[tex]9.8*443 = \frac{1}{2} v_f^2 + 9.8*221[/tex]
[tex]2175.6 = \frac{1}{2}v_f^2[/tex]
[tex]v_f = 65.96 m/s[/tex]
so final speed will be 65.96 m/s